2016
DOI: 10.5001/omj.2016.09
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcome of Patients with Cardiogenic Shock Complicating Acute Myocardial Infarction: Results from Royal Hospital Percutaneous Coronary Intervention Registry, Oman

Abstract: CS in AMI patients presenting to a tertiary hospital in Oman have high in-hospital mortality despite the majority undergoing PCI. Even though the in-hospital mortality is comparable to other studies and registries, there is an urgent need to determine the causes and find any remedies to provide better care for such patients, specifically concentrating on the early transfer of patients from regional hospitals for early PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The above finding could be due to inadequate use of reperfusion therapy [62]. However, a retrospective study conducted in Oman reported that out of 63 ACS patients having cardiogenic shock, the in-hospital mortality was 52.4%, even though 93.6% of them underwent PCI [63]. This difference could be due to sample size variation and timing of the therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The above finding could be due to inadequate use of reperfusion therapy [62]. However, a retrospective study conducted in Oman reported that out of 63 ACS patients having cardiogenic shock, the in-hospital mortality was 52.4%, even though 93.6% of them underwent PCI [63]. This difference could be due to sample size variation and timing of the therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years in-hospital deaths due to cardiac causes have been increasing in Oman, especially among patients presenting with ACS [13]. However recent improvements in healthcare for patients with heart diseases have led to increased survival and reduced length of stay in acute care settings by patients with myocardial infarction [14].…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Currently, the mortality rates of CS still remain unacceptably high exceeding 50%, which is the leading cause of in-hospital mortality despite significant advancements in aggressive guideline-directed medical therapy and early reperfusion therapy. 7 , 8 Hence, it is clinically significant to identify a novel biomarker to predict in-hospital mortality in CS patients with high accuracy.…”
Section: Introductionmentioning
confidence: 99%